Post a New Question

Alg 2

posted by .

By what amount does the sum of the roots exceed the product of the roots of the equation (x-7)(x+3)=0?

I have no idea what to do!

  • Alg 2 -

    first get the roots,,
    (x-7)(x+3)=0
    thus equating each term inside the parenthesis to zero,
    x-7=0 and x+3=0
    therefore, x=7 and x=-3
    the roots are 7 and -3
    sum: 7 + (-3) = 4
    product: 7(-3) = -21
    the questions asks for the difference between the sum and product, therefore:
    4 - (-21) = 25

    hope this helps~ :)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question